(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the features of some plug-in sounds in the Kazakh language. In linguistics, there are several phonetic processes. Of these, prosthesis, epenthesis, epiteza are less common. However, the study of these phonetic processes is the question of the future. Usually, the plug–in sounds are regarded as sounds that join at the beginning of words, middle and end of a word. Consonants and vowels can serve as plug-in. Undoubtedly, the study of plug-in sounds requires a lot of effort and it is a very complex topic. The article discusses that to determine the plug-in sounds, special attention is paid to the borrowed words. Examples of Arabic-Persian and Russian words are given in the paper. It is indicated that determination of historical descriptions of the plug-in sounds requires a lot of work.